Senior Secondary School Teachers’ Test Construction Skill and Testing Practices (2022)
The study assessed the extent to which teachers in senior secondary school applied principles of test construction and administration in senior secondary school in some selected school in Oyo state. The descriptive research design of survey type was used for the study. Simple random sampling procedure was used to include 533 senior secondary school teachers in Oyo state for the study. Three research questions guided the study. A 16-item, 16-items and 23-item questionnaires for teachers were used for data collection. The Cronbach’s coefficient alpha for the teachers questionnaires were 0.73, 0.65 and 0.78 respectively. The results showed that, to a great extent, teachers were not aware of the test construction principles. Also, the results showed that, the teachers were not aware of the meaning of test construction terminologies. Again, it was found out that teachers of senior secondary school were not aware of the test administration principles. Students were made aware of the time the exams will start and the subjects to be written each day and nothing more. It is recommended that teachers are given timely in-service training on test item construction and administration. Furthermore, Oyo state teaching service commission should allocate funds for workshops, seminars and others for teachers on test item construction and administration